Análisis de la utilización de recursos didácticos en el proceso de enseñanza aprendizaje de la matemática, en la unidad educativa la providencia periodo enero 2017- abril 2017. - Ipiales Guala, Olga Tatiana (2017)
Mathematics is one of the subjects that many students do not like which can be caused by several factors, one of them may be due the way of teaching by the professor, in that sometimes they are limited and it is done in a traditional form, the teacher nowadays has a great variety of didactic resources that can be deliver education. The purpose of this research is to identify the type of didactic resources used in the teaching process of mathematics at "La Providencia" Educational Unit from January 2017 - April 2017. The theoretical framework is the conceptual analysis of different authors and other media, the same ones that included in the bibliography. The design of the research is non-experimental, level of descriptive research and the type of research is descriptive, bibliographical and field. The population is made up of two teachers and 210 students. Through this research it has been possible to conclude that the teachers know about the didactic resources and use them, it is possible to emphasize that the teachers have knowledge on the subject but they usually use more of the didactic traditional resources as the didactic boards. The teaching resources allow the student to have a better learning and thus can improve every day, in addition the teacher must always be dynamic and innovative and must continually research the most appropriate way to reach their students and motivate them to have more interest in learning Mathematics and one of the ways is to use all means or didactic resources that are possible as long as they are used correctly only so the student can create a correct learning and therefore motivate.